Effects of neuromuscular electrical stimulation and core muscle strengthening on trunk instability following stroke - K. B., Riyas Basheer; K. V., Dinesh; Rai, Subhashchandra; A. T., Mohammed Arshak (International Journal of Research in Medical Sciences, 2021)
Background: Postural instability leads to balance dysfunction in stroke subjects, which always increase the risk of fall. This study aimed to compare the effect of neuromuscular electrical stimulation and core muscle strengthening on trunk balance following stroke. Methods: Forty five stroke subjects were participated and assigned randomly into three groups; all groups received standard rehabilitation program; and core group received additional core strengthening, neuromuscular electrical stimulation (NMES) group received added electrical stimulation over paraspinal region and combination group received core muscle strengthening and NMES along with standard rehabilitation protocol. After four weeks of the interventions, primary and secondary outcome measures are evaluated. Berg Balance Scale (BBS), Postural Assessment Scale for Stroke (PASS), Trunk Impairment Scale (TIS) and Barthel Index (BI) were evaluated before and after the intervention. Results: All the three (core MS, NMES and combination) groups showed significant improvement after the intervention (BBS 10.07, 15.54 and 18.27, PASS 6.54, 13.06 and 14.00, TIS 0.25, 0.25 and 0.51, BI 16.40, 29.93 and 36.53). The combination group (NMES and core muscle strengthening) showed better improvement than other two groups. TIS and BI total score showed positive (0.849) correlation. Conclusions: Addition of NMES along with core muscle strengthening for stroke rehabilitation will improve trunk stability, balance and ADLs.